2015
DOI: 10.1093/cercor/bhv060
|View full text |Cite
|
Sign up to set email alerts
|

Visual Contrast Sensitivity Improvement by Right Frontal High-Beta Activity Is Mediated by Contrast Gain Mechanisms and Influenced by Fronto-Parietal White Matter Microstructure

Abstract: Behavioral and electrophysiological studies in humans and non-human primates have correlated frontal high-beta activity with the orienting of endogenous attention and shown the ability of the latter function to modulate visual performance. We here combined rhythmic transcranial magnetic stimulation (TMS) and diffusion imaging to study the relation between frontal oscillatory activity and visual performance, and we associated these phenomena to a specific set of white matter pathways that in humans subtend atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 59 publications
7
69
0
Order By: Relevance
“…, , , and ). Similar results have been obtained with rhythmic TMS . Overall, these studies suggest that frequency‐tuned noninvasive brain stimulation can modulate brain oscillations to clarify their role in brain functions.…”
Section: Frequency‐tuned Transcranial Brain Stimulationsupporting
confidence: 84%
“…, , , and ). Similar results have been obtained with rhythmic TMS . Overall, these studies suggest that frequency‐tuned noninvasive brain stimulation can modulate brain oscillations to clarify their role in brain functions.…”
Section: Frequency‐tuned Transcranial Brain Stimulationsupporting
confidence: 84%
“…For the documentation of entrainment effects, control conditions with different temporal patterns should also be considered, including stimulation at different frequencies, e.g., at both higher and lower neighboring frequencies (Romei et al, 2010, 2015, Chanes et al 2013) as well as arrhythmic (trial to trial randomized pulse timing) and rhythmic irregular (fixed pulse timing at unequal intervals) stimulation protocols (Thut et al, 2011, Chanes et al 2013, Chanes et al 2015, Quentin et al 2015b), or using another montage stimulating task-irrelevant areas but at the target frequencies. If TACS has a DC-offset (so called oscillatory TDCS, oTDCS), there needs to be a control for mere effects of DC, as oTDCS should have the same effects as TDCS as long as total charge is matched (Bergmann et al, 2009, Groppa et al, 2010).…”
Section: Methodological Considerations: Proper Documentation Of Efmentioning
confidence: 99%
“…In terms of immediate effects during NTBS, there are multiple examples that this approach may indeed lend itself for a targeted intervention into oscillatory brain activity through entrainment that can affect brain function and behavior, both using TMS or TACS (for TMS examples see, Klimesch et al, 2003, Sauseng et al, 2009b, Romei et al, 2010, 2015, Thut et al, 2011, Chanes et al, 2013, Chanes et al, 2015, Hanslmayr et al, 2014, Ruzzoli and Soto-Faraco, 2014, Jaegle and Ro, 2014, Quentin et al, 2015a; Quentin et al, 2015b; for TACS examples see, Pogosyan et al, 2009, Feurra et al, 2011, Joundi et al, 2012, Neuling et al, 2012, Santarnecchi et al, 2013, Helfrich et al, 2014b, Cecere et al, 2015, Witkowski et al, 2015, Chander et al, 2016, Ruhnau et al, 2016, Guerra et al, 2016). However, most of the evidence for the existence of entrainment effects comes from behavioral studies.…”
Section: What Is the Empirical Support That Tuning Ntbs To Oscillamentioning
confidence: 99%
“…Subsequently, it has been demonstrated that the instantaneous percept depended on the level of inter-hemispheric gamma-band synchrony, which could selectively be modulated by tACS [90]. Taken together, these findings highlight that synchronized oscillatory brain activity is mediated by cortico-cortical connections between specialized regions to facilitate cortical information transfer and integration within narrow frequency-bands [9193]. …”
Section: Linking Structural and Functional Connectivitymentioning
confidence: 99%